Engineering problem solving with ANSI C fundamental concepts - Etter, Delores M. (Prentice Hall, 1996)
This work features a wide variety of real-world applications of usable C code, to solve problems in electrical, computer, mechanical, civil and environmental engineering, as well as the computer sciences. It provides state-of-the-art ANSI C programs, showing top-down design and stepwise refinement with the use of decomposition outlines and pseudocode. The book features practical real-world engineering and scientific examples, and discusses numerical techniques that are commonly used in solving engineering problems. The accompanying disk contains all the example programs and data files presented in the book.